Relationship between the opponent block and the hitter in elite male volleyball - Araujo, R. M.; Castro, J.; Marcelino, R.; Mesquita, I. R. (Journal of Quantitative Analysis in Sports, 2010)
The purpose of this study was to examine the relationship between the opponent block, i.e. the blockers starting points and the number of blockers, compared to the hitter chosen by the setter to attack in elite male volleyball competition. 4531 sequences were analyzed, corresponding to 97 sets, of 12 national male teams participating in the 2007 World Cup. In order to test the association between variables, descriptive and inferential statistics the chi-square test with analysis of the adjusted residual were used. Intra- and inter-observer reliability was assessed via the percentage error method. Results showed that the pinched block "starting point" and the double block "final blocking action" were the most recurrent ones and the opposite player (right side) was the most requested hitter. This study showed a significant association between the blockers starting points and the hitter chosen by the setter to finalize the play set. There was a downward trend in the attack from the middle hitter with pinched block and an upward trend in the attack of the opposite (right side) with mixed block (pinched zone 2). A significant association between hitter and number of blockers was also verified: middle hitters show a high tendency to attack facing individual block, opposite players (right side) usually attack vs. double block and left-side hitters usually face double and triple block. These results suggest that blocker`s starting points are taken in consideration by the opponent setter to create the best conditions for the hitters. Hence, the setter takes advantages of the specific features (skills and ability to score) of its hitters and the space where they perform the attack in order to create difficulties to the opponent block (i.e. middle hitters has a high trend to attack with individual block, opposite player with double block and left-side hitters with double and triple block). The present study shows that the volleyball game at the elite male level is characterized by a constant adaptation between setter`s options and the opponent block tactics and strategies. These trends must be considered in the training process to prepare hitters and blockers for the most common situations occurring in the competition and, therefore, to create better and more appropriated and effective solutions to the game problems.